Energy Investment Risk Assessment for Nations Via Seq2seq Model - Liang, Panning; Yu, Mingyang; Jiang, Lincheng (Frontiers in Environmental Science, 2021)
China's "Belt & Road Initiative" has been proposed for several years, which has stimulated the economic and financial development of the countries alongside the "Belt & Road". For a world's leading energy consuming country, China tries to secure the energy supply from the resource-rich countries via oversea energy investment. In this paper, we propose a seq2seq model to evaluate the energy investment risk of 50 countries alongside the "Belt & Road Initiative". Specifically, we first build an indicator system mainly containing six factors. Then we adopt Bi-LSTM as encoder to process the historical statistics. Afterwards, we use self-attention mechanism to assign the weights on the six factors of the indicator system. Finally we use a hierarchical CNN decoder to generate the assessment results. Our findings indicate that resource potential and Chinese factor are the most important indicators. And through our thorough investigation, we find that Russia, Kazakhstan, Pakistan, UAE, Saudi Arabia, Malaysia and Indonesia are the most recommended target countries for China's oversea energy investment.